Effect of Cyclotrimethylenetrinitramine on Wet Synthesis of Ultra-Nanocrystalline Diamond - Amin, M.H.; Akbar Mottalebizadeh, Ali; Borji, Saeid (Asian Journal of Chemistry, 2010)
The ultra-nanocrystalline diamond was synthesized by the detonation of a high explosive mixtures in water confinement. The presence of a diamond phase was revealed by X-ray diffraction and transmission electron microscopy. X-Ray line broadening was used to evaluate the peak profiles of diamond nanoparticles and their corresponding average crystallite sizes. The micro structure of nanocrystalline diamond have been investigated by high resolution transmission electron microscopy. The results indicate that the optimum of cyclotrimethylenetrinitramine addition on 2-methyl-1,3,5-trinitrobenzene is 60 % and the size of nanodiamond particle was about 5 nm.